Association Between Prospective Registration and Quality of Systematic Reviews in Type 2 Diabetes Mellitus: A Meta-epidemiological Study - Zheng, Qiuyi; Lai, Fenghua; Li, Bin; Xu, Jia; Long, Jianyan; Peng, Sui; Li, Yanbing; Liu, Yihao; Xiao, Haipeng (Frontiers in medicine, 2021)
Background: We sought to investigate the methodological and reporting quality of published systematic reviews describing randomized controlled trials in type 2 diabetes mellitus and analyze their association with status of protocol registration. Methods: We searched the PubMed database and identified non-Cochrane systematic reviews, with or without meta-analysis, reporting on type 2 diabetes mellitus and published between 2005 and 2018. We then randomly selected 20% of these reviews in each year, and performed methodological and reporting quality assessment using the Assessment of Multiple Systematic Review 2 (AMSTAR-2) checklist and Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement. We also conducted regression analyses to explore the association between characteristics of systematic reviews and AMSTAR-2 or PRISMA scores. Results: A total of 238 systematic reviews, including 33 registered and 205 non-registered articles, met the inclusion criteria and were subsequently reviewed. Analysis indicated an increase in both registered rates and quality of systematic reviews in type 2 diabetes mellitus over the recent years. With regards to methodological and reporting quality, we found higher scores in registered, relative to non-registered reviews (AMSTAR-2 mean score: 18.0 vs. 14.5, P = 0.000; PRISMA mean score: 20.4 vs. 17.6, P = 0.000). AMSTAR-2 and PRISMA scores were associated with registration status, country of the first author, and statistical results, whereas the proportion of discussing publication bias and reporting funding sources were <40% for both registered and non-registered systematic reviews. Conclusions: Methodological and reporting quality of systematic reviews in type 2 diabetes mellitus indicates an improvement in the recent years. However, the overall quality remains low, necessitating further improvement. Future studies are expected to pay more attention to prospective registration, description of publication bias and reporting of funding sources.